2010
DOI: 10.1176/appi.ajp.2010.09081187
|View full text |Cite
|
Sign up to set email alerts
|

The Hippocampal Formation in Schizophrenia

Abstract: The hippocampal formation is one of the most extensively studied regions of the brain, with well-described anatomy and basic physiology; moreover, aspects of human memory mediated by the hippocampus are well characterized. In schizophrenia, alterations in hippocampal anatomy, perfusion, and activation are consistently reported; impairments in declarative memory function, especially in the flexible use of event memories (e.g., in the service of memory-based inference), are common. Postmortem molecular changes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
460
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 518 publications
(494 citation statements)
references
References 234 publications
28
460
1
Order By: Relevance
“…In line with a recent study that reported greater hippocampal shape alterations in patients with schizophrenia and prior comorbid alcohol use disorders (Smith et al, 2011), we hypothesised that cannabis use would exert an additional effect on the hippocampal pathology typically observed in schizophrenia, particularly in the anterior hippocampus (Csernansky et al, 2002;Small et al, 2011;Tamminga et al, 2010).…”
Section: Introductionsupporting
confidence: 64%
“…In line with a recent study that reported greater hippocampal shape alterations in patients with schizophrenia and prior comorbid alcohol use disorders (Smith et al, 2011), we hypothesised that cannabis use would exert an additional effect on the hippocampal pathology typically observed in schizophrenia, particularly in the anterior hippocampus (Csernansky et al, 2002;Small et al, 2011;Tamminga et al, 2010).…”
Section: Introductionsupporting
confidence: 64%
“…Neuropathological studies of people with schizophrenia indicate the presence of cytoarchitectural abnormalities within cortical grey matter and particularly in hippocampus, typically reduced hippocampal volume (Tamminga et al, 2010). However, such findings are not always replicated (particularly if controls are family members) (Gothelf et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A consistent neuropathology in SZ is the subtle disruption of the anterior aspect of the hippocampal formation (Goldman and Mitchell, 2004;Harrison, 2004;Tamminga et al, 2010). While the specific, persistent chemoanatomical disruptions in the maturation of the hippocampus and its target regions following TTX on PD7 remain to be determined, they are likely to be more representative than the large, gross lesions produced by early ibotenic acid lesions of the VH.…”
Section: Ttx-induced Inactivation Of Developing Vh As An Animal Modelmentioning
confidence: 99%